Pre- and post-embryonic haemoglobin variations in guineafowl - PAL, S K; SINGH, HARPREET (The Indian Journal of Animal Sciences, 2013)
Guineafowl haemoglobin electrophoretic components revealed a typical avian pattern, consisting of a major and a minor component. Keets and growers up to 20 weeks of age also revealed another slow-moving minor band suggesting the presence of embryonic haemoglobin component Hb-H. Five embryonic baemoglobin components, viz. A, D, p. E and H, were identified. Embryonic to adult haemoglobin switchover was observed around day 9 of incubation. A variant phenotype was observed in 3% embryos.